CHALLENGES OF ONLINE TEACHING DURING THE COVID-19 PANDEMIC - Malogorski Jurjević, Martina; Đuranović, Marina; Olčar, Diana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The teaching profession has always been complex and dynamic, but now the challenges are posed to a society as a whole by the COVID-19 pandemic. The purpose of the research was to determine teachers' perceptions of the challenges of conducting online teaching during the COVID-19 pandemic. 413 teachers from Croatia participated in the research. Respondents were distributed according to the level of education at which they work in three groups (primary school teachers - grades 1st to 4th, subject teachers – grades 5th to 8th of primary school, subject teachers - secondary school). According to the results of the research, teachers estimated that difficulties in online teaching generally occur occasionally. There were statistically significant differences in some of the items in the perception of the challenges in online teaching among teachers depending on the level of education at which they work. Still, in general, teachers at all three levels of education experienced approximately the same amount of challenges. More challenges in online teaching have been related to a higher level of burnout and correlated positively with higher numbers of students to teach. Age has been unrelated to challenges in online teaching. Since difficulties in conducting online teaching hinder the educational process, this research could serve as an indicator of problems and an initial step to solving them.